Cellular therapy of corneal epithelial defect by adipose mesenchymal stem cell-derived epithelial progenitors - Bandeira, Francisco (2021)
Background: Persistent epithelial defects (PED), associated with limbal stem cell deficiency (LSCD), require ocular surface reconstruction with a stable corneal epithelium (CE). This study investigated CE reformation using human adipose mesenchymal stem cells (ADSC), which derived epithelial progenitors via mesenchymal-epithelial transition (MET). Methods: STEMPRO human ADSC were cultured with specific inhibitors antagonizing glycogen synthase kinase-3 and transforming growth factor-β signaling, followed by culture under a defined progenitor cell targeted-epithelial differentiation condition to generate epithelial-like cells (MET-Epi), which were characterized for cell viability, mesenchymal, and epithelial phenotypes using immunofluorescence and flow cytometry. Tissue-engineered (TE) MET-Epi cells on fibrin gel were transplanted to corneal surface of the rat LSCD model caused by alkali injury. Epithelial healing, corneal edema, and haze grading, CE formation were assessed by fluorescein staining, slit lamp bio-microscopy, anterior segment optical coherence tomography, and immunohistochemistry. Results: CD73high/CD90high/CD105high/CD166high/CD14negative/CD31negativehuman ADSC underwent MET, giving viable epithelial-like progenitors expressingδNp63, CDH1 (E-cadherin), epidermal growth factor receptor, integrin-β4, and cytokeratin (CK)-5, 9. Under defined epithelial differentiation culture, these progenitors generated MET-Epicells expressing cell junction proteins ZO1 and occludin. When transplanted onto rat corneal surface with LSCD-induced PED, TE-MET-Epi achieved more efficient epithelial healing, suppressed corneal edema, and opacities, when compared to corneas without treatment or transplanted with TE-ADSC. CE markers (CK3, 12, and CDH1) were expressed on TE-MET-Epi-transplanted corneas but not in other control groups. Conclusion: Human ADSC-derived epithelial-like cells, via MET, recovered the CE from PED associated with LSCD. ADSC can be a viable adult stem cell source for potential autologous epithelial cell-based therapy for corneal surface disorders.